2016
DOI: 10.1371/journal.pone.0161357
|View full text |Cite
|
Sign up to set email alerts
|

Gender Representation on Journal Editorial Boards in the Mathematical Sciences

Abstract: We study gender representation on the editorial boards of 435 journals in the mathematical sciences. Women are known to comprise approximately 15% of tenure-stream faculty positions in doctoral-granting mathematical sciences departments in the United States. Compared to this group, we find that 8.9% of the 13067 editorships in our study are held by women. We describe group variations within the editorships by identifying specific journals, subfields, publishers, and countries that significantly exceed or fall … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
108
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 26 publications
(33 reference statements)
3
108
1
Order By: Relevance
“…In the geosciences, for example, although there are significant numbers of women earning geoscience degrees in the US ) these numbers are not translating into equivalent female representation in academic faculty (Glass 2015) or professional activities such as journal refereeing (Lerback and Hanson 2017). Similarly, lower than expected representation of women has been observed in editorial boards in mathematics (Topaz and Sen 2016) and as invited conference speakers in ecology and conservation (Schroeder et al 2013;Sardelis and Drew 2016). Women of colour are even more under-represented across STEM degrees and positions, with representation declining with increasing seniority (Ong et al 2011;Ballenger et al 2017).…”
Section: Introductionmentioning
confidence: 98%
“…In the geosciences, for example, although there are significant numbers of women earning geoscience degrees in the US ) these numbers are not translating into equivalent female representation in academic faculty (Glass 2015) or professional activities such as journal refereeing (Lerback and Hanson 2017). Similarly, lower than expected representation of women has been observed in editorial boards in mathematics (Topaz and Sen 2016) and as invited conference speakers in ecology and conservation (Schroeder et al 2013;Sardelis and Drew 2016). Women of colour are even more under-represented across STEM degrees and positions, with representation declining with increasing seniority (Ong et al 2011;Ballenger et al 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Women remain underrepresented among reviewers of journal papers (Fox, Burns, & Meyer, 2016a;Helmer, Schottdorf, Neef, & Battaglia, 2017;Lerback & Hanson, 2017). Women also remain underrepresented among the gatekeepers of scientific publishing; while representation varies substantially among disciplines and among journals within disciplines (Amrein, Langmann, Fahrleitner-Pammer, Pieber, & Zollner-Schwetz, 2011;Morton & Sonnad, 2007;Topaz & Sen, 2016), when compared to the gender of authors in a journal, women are underrepresented on editorial boards (Fox, Burns, & Meyer, 2016a;Helmer et al, 2017;Manlove & Belou, 2018;Topaz & Sen, 2016;Wehi, Beggs, & Anderson, 2019), especially at more senior editorial levels, for example, editors in chief (Amrein et al, 2011;Cho et al, 2014). While it is clear that women are underrepresented as reviewers and editors, we still lack a clear understanding of the causes and consequences of this gender disparity.…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity for homophilous interactions is determined by the demographics of the 572 gatekeeper pool, and the demographics of the gatekeepers differed significantly from those of 573 the authors, even for last authors, who tend to be more senior [59][60][61][62]. The underrepresentation 574 of women at eLife mirrors global trends-women comprise a minority of total authorships, yet 575 constitute an even smaller proportion of gatekeepers across many domains [14, [67][68][69][70][71][72][73][74]. Similarly, 576 gatekeepers at eLife were less geographically diverse than their authorship, reflecting the general 577 underrepresentation of the "global south" in leadership positions of international journals [75].…”
mentioning
confidence: 99%
“…Increasing representation of women and scientists from a more diverse set of nations among 588 eLife's editor may lead to more diverse pool of peer reviewers and reviewing editors and a more 589 equitable peer review process. Editors often invite peer reviewers from their own professional 590 networks, networks that likely reflect the characteristics of the editor [76][77][78]; this can lead to 591 editors, who tend to be men [14, [67][68][69][70][71][72][73][74] and from scientifically advanced countries [75] to invite 592 peer reviewers who are demographically similar to themselves [44,79,80], inadvertently 593 excluding certain groups from the gatekeeping process. Accordingly, we found that male 594…”
mentioning
confidence: 99%